MANAGEMENT OF FULL DAY SCHOOL TOWARDS STRENGTHENING THE VALUES OF ISLAMIC EDUCATION - Arifin, Zainal; Mawardi, Imam (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The purpose of this research is to find out and describe (1) the concept of implementing full day school management in strengthening the values of Islamic education in SD Muhammadiyah 1 Denpasar, (2) inhibiting and supporting factors, (3) solutions to overcome obstacles. Descriptive research method with a qualitative approach, data collection, observation, interviews, and documentation. The results of the research that; (1) the concept applied at SD Muhammadiyah 1 Denpasar is full day school with a focus on strengthening the values of Islamic education. Implementation of full day school by strengthening the values of Islamic education aims to make students have good morals and character through habituation, daily prayer and dhikr, dhuha prayer, recitation, and obligatory prayer in congregation, (2) the inhibiting factor is the input variety, location and school regulations. The supporting factors are the support from teachers, parents, and the organization, and (3) intense coaching is provided by bringing in special ustadz and ustadzah to teach students to recite and memorize the Quran (tahfidz), carry out daily worship habits, increase activities that breathe Islamic education, build good communication and cooperation with parents of students. The conclusion is that the full day school concept applied is a full day school with the strengthening of Islamic educational values implemented through various habituation activities. Various inhibiting and supporting factors arise from within and outside, but can be overcome with solutions in the form of coaching and communication.